Introduction to the special issue: Applying a Caribbean perspective to an analysis of HIV/AIDS. Issue 11 (2nd November 2019) - Hintzen, Percy; Vertovec, John; Cyrus, Elena; Padilla, Mark; Varas-Díaz, Nelson
ABSTRACT: This introduction presents a special issue of Global Public Health with a collection of articles that offer multidisciplinary perspectives on HIV/AIDS in the Caribbean. Since the 1990s, poverty, marginalisation, and social stigma have been strong foci of much social science research on HIV/AIDS in the region. These three interrelated phenomena have been offered as explanatory factors contributing to the high prevalence of cases observed in this region. Contributors to this special issue take these emphases in new directions, asking multi-level questions that require unique combinations of epidemiological, social scientific, theoretical, and policy-oriented perspectives and methodologies. Together, they identify several topical areas that intend to create dialogue across disciplines and dialectics, with the fundamental principle that the factors relevant to HIV/AIDS are broad and require intersectional lenses. The articles in this issue offer multi-level interventions into HIV/AIDS in the region, from the varied social circumstances that shape heightened risk factors to patient adherence programmes, with emphases on structural, social, and policy-level approaches. Collectively, this special issue establishes the importance of transdisciplinary approaches to HIV/AIDS that are macro-level in scope, but simultaneously attend to how large-scale dynamics are inflected in situated contexts and histories.